The convergence of Iteration Scheme to Fixed Points in Modular Spaces - Abduljabbar, Meena Fouad; Abed, Salwa Salman (Iraqi Journal of Science, 2019)
The aim of this paper is to study the convergence of an iteration scheme for multi-valued mappings which defined on a subset of a complete convex real modular. There are two main results, in the first result, we show that the convergence with respect to a multi-valued contraction mapping to a fixed point. And, in the second result, we deal with two different schemes for two multivalued mappings (one of them is a contraction and other has a fixed point) and then we show that the limit point of these two schemes is the same. Moreover, this limit will be the common fixed point the two mappings.